Perceived Risk Analysis of and Willingness to Buy Food Nanotechnology - Fidyani, Citra; Satria, Arif; Kirbrandoko, Kirbrandoko (Jurnal Manajemen dan Agribisnis, 2019)
A number of studies stated that nanotechnology is predicted to encourage the third wave of research diffusion, development, and advancement in agricultural and food sectors, as an integrated part of the nanotechnology revolution in various fields. The aim of this study was to assess the effect of nanotechnology knowledge, trust, and communication media on perceived risk and willingness to buy food nanotechnology. The data came from an online questionnaire with 302 people collected by an online survey, and the research used a purposive sampling method, and structural equation modeling was used for data analysis. Based on the result of the research on three variables (nanotechnology knowledge, trust, and communication media), it is known that communication media and trust had significant effects on risk perception; however, nanotechnology knowledge had no significant effect. Furthermore, perceived risk had a significant effect on willingness to buy food nanotechnology. The sequence from the largest to the smallest of willingness to buy is functional food with a health benefit, food packaging, and food additive to improved product quality. Functional food has been chosen because there is an additional health benefit they will get. Meanwhile, food packaging was considered less risky as it did not directly contact with the product and was not digested by the body. Food additives to improve product quality was the lowest since the respondents felt they did not get any benefits from the application.